Black images in the comics : a visual history - d; Johnson, Charles, 1948- ([Seattle, WA] : Fantagraphics Books, 2012)
This book spotlights over 100 comic strips, comic books, and graphic novels to feature black characters from all over the world over the last century, and the result is a fascinating journey to, if not enlightenment, then at least away from the horrendous caricatures of yore. ... Each strip, comic, or graphic novel is spotlighted via a compact but instructive 200-word essay and a representative illustration [in black and white]. The book is augmented by a context-setting introduction, an extensive source list and bibliography, and a foreword by Charles R. Johnson, the recipient of a MacArthur Foundation fellowship and winner of the National Book Award for his 1990 novel Middle Passage.--Publisher's description.
Originally published: 2003.
Includes bibliographical references (pages 274-[287]) and index.
Keywords: Comic books, strips, etc. -- History and criticism; Blacks in art; Blacks in literature